2023
DOI: 10.3389/fimmu.2023.1055256
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 17 B regulates colonic myeloid cell infiltration in a mouse model of DSS-induced colitis

Abstract: Cytokines play vital roles in the pathogenesis of inflammatory bowel disease. IL17B is protective in the development of colitis. However, how IL17B regulates intestinal inflammation and what cells are regulated by IL17B is still unknown. Here, we aimed to illustrate the IL17B dependent cellular and molecular changes in colon tissue in a mouse colitis model. The results showed that IL17B expression in colon tissues was elevated in inflamed tissues than non-inflamed tissues of IBD patients. Wild type (WT) and Il… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…However, there are few studies on IL-17B in IBD. One of the few existing studies suggested that IL-17B regulates the response of colonic myeloid cells to inhibit colitis ( 59 ), which is the same as the results of this study. IL-17A is generally considered to play a promoting role in NAFLD, while IL-17F has been reported to play a role in preventing liver function damage in NAFLD ( 60 ), which is also consistent with the results of this study.…”
Section: Discussionsupporting
confidence: 90%
“…However, there are few studies on IL-17B in IBD. One of the few existing studies suggested that IL-17B regulates the response of colonic myeloid cells to inhibit colitis ( 59 ), which is the same as the results of this study. IL-17A is generally considered to play a promoting role in NAFLD, while IL-17F has been reported to play a role in preventing liver function damage in NAFLD ( 60 ), which is also consistent with the results of this study.…”
Section: Discussionsupporting
confidence: 90%
“…35 Damage to the intestinal mucosal barrier can result from increased leukocyte infiltration (CD45 positive cells) in the colon. 36 Our immunohistochemical results showed that the number of CD45 positive cells in the colon was significantly higher in the DSS-alone group as compared to that in the control group. The effect was significantly reduced after 2-week recovery.…”
Section: Resultsmentioning
confidence: 58%
“…To focus on the development of this methodology, we opted for IHC targets that have already been utilized in existing literature. We plan to introduce functional markers in future work, especially considering the growing application of single cell studies to mouse models of colitis 51 53 .…”
Section: Discussionmentioning
confidence: 99%